Climate Change Education in Finland - Yli-Panula Eija; Jeronen Eila Kyllikki; Mäki Sanna (MDPI, 2026)
The climate change education (CCE) is understood as a component of environmental education and education for sustainable development. Its core concept is CC literacy, which means that students understand the scientific concepts related to CC and the relationships between them, as well as the effects of CC and their own activities on the environment. CCE is multidisciplinary and interdisciplinary. Multidisciplinarity means that knowledge of various individual sciences is needed. Interdisciplinarity, on the other hand, incorporates elements from a variety of disciplines and also integrates environmental, economic, social and political issues.